Monophonic wirelength on Circulant Networks - Uma Samundesvari, K; G. Michael, Sindhuja (International Journal of Engineering and Technology, 2018)
In this paper, we define the monophonic embedding of graph G into graph H and we present an algorithm for finding the monophonic wirelength of circulant networks into the family of grids M(nÃ—2), nâ‰¥2.The monophonic embedding of a graph G into a graph H is an embedding denoted by fm is a bijective map from the vertex set of G into the vertex set of H and fm is a one-one mapping from the edge set (x, y) of G into Pm(H) where Pm(H) is the set of monophonic paths between fm(x) and fm(y) for every fm(x), fm(y) H. The monophonic wirelength of fm of G into H is the sum of distances of monophonic paths between two vertices fm(x) and fm(y) in H such that (x, y) E(G). This paper presents a monophonic algorithm to find the monophonic wirelength of circulant networks G(2n, Â±S) , where S 1,2,3,â€¦,n into the family of grids M[nÃ—2],nâ‰¥2. We also derived a Lemma to get the monophonic edge congestion MEC(G,H).Â Â